The Baptist Health High-Risk Falls Assessment: One Assessment Fits All. Issue 2 (April 2017) - Bugajski, Andrew; Lengerich, Alex; McCowan, Denise; Merritt, Sharon; Moe, Krista; Hall, Brittany; Nelson, Debbie; Brockopp, Dorothy
Abstract : Assessing high risk for falling among psychiatric inpatients is particularly challenging in that assessments with strong sensitivity and specificity are not available. The purpose of this study was to determine the sensitivity, specificity, and diagnostic odds ratio of the Baptist Health High Risk Falls Assessment (BHHRFA), a medical-surgical fall risk assessment, in a psychiatric inpatient population. Data collected on 5910 psychiatric inpatients using the BHHRFA showed acceptable sensitivity, specificity, and diagnostic odds ratio (0.68/0.70/4.964). Abstract : Supplemental Digital Content is Available in the Text.